Long-Term Trends and Impact of SARS-CoV-2 COVID-19 Lockdown on the Primary Productivity of the North Indian Ocean - Sunanda, N.; Kuttippurath, J.; Peter, R.; Chakraborty, Kunal; Chakraborty, A. (Frontiers in Marine Science, 2021)
COronaVIrus Disease (COVID) 2019 pandemic forced the countries to go into complete lockdown and India went on complete lockdown from March 24th – June 8th 2020. In order to understand the possible implications of lockdown, we analyse the long-term distribution of Net Primary Productivity (NPP) in the north Indian Ocean (NIO) and the factors that influence NPP directly and indirectly, for the period 2003–2019 and 2020 separately. There exists a seasonal cycle in the correlation between AOD, Chlorophyll–a (Chl–a) and NPP in agreement with the seasonal transport of aerosols and dust into these oceanic regions. In Arabian Sea (AS), the highest Chl–a (0.58 mg/m3), NPP (696.57 mg/C/m2/day) and AOD (0.39) are observed in JJAS (June, July, August and September) and In BoB, maximum Chl–a (0.48 mg/m3) and NPP (486.39 mg/C/m2/day) are found in JJAS and AOD (0.27) in MAM (March, April and May). The interannual variability of Chl–a and NPP with wind speed and Sea Surface Temperature (SST) is also examined, where the former has a positive and the latter has a negative feedback to NPP. The interannual variability of NPP reveals a decreasing trend in NPP, which is interlinked with the increasing trend in SST and AOD. The analysis of wind, SST, Chl–a, and AOD for the pre-lockdown, lockdown, and post lockdown periods of 2020 is used to understand the impact of COVID-19 lockdown. The assessment shows the reduction in AOD, decreased wind speeds, increased SST and reduced NPP during the lockdown period as compared to the pre-lockdown, post-lockdown and climatology. The year 2018 is also analysed separately during these periods to understand the influence of lockdown in NIO. This analysis will help to understand the impact of aerosols on the ocean biogeochemistry, nutrient cycles in the ocean biogeochemical models, and to study the effects of climate change on ocean ecosystems.